2022
DOI: 10.3389/fsurg.2022.922139
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous kyphoplasty for the treatment of diffuse idiopathic skeletal hyperostosis with vertebral fractures: A case report and treatment review

Abstract: Diffuse idiopathic skeletal hyperostosis (DISH) is a systemic metabolic condition characterized by new bone formation mainly at the anterolateral spine. Surgery such as screw fixation is commonly used for DISH patients who also suffer from vertebral fractures. In this case report, we share a DISH case with lumbar vertebral fracture and osteoporosis who underwent percutaneous kyphoplasty plus braces and medication. Percutaneous kyphoplasty, considered as minimally invasive surgery, may be another treatment opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…9 There are also a few previous reports of successful percutaneous vertebroplasties for vertebral fractures in patients with DISH. 12,23 The present study showed that fractures of the most distal or distal-adjacent vertebrae of ankylosing spines were stabilized by bone healing in 51/89 patients (57.3%) 6 months after BKP. In addition, fractures of the vertebrae adjacent to the ankylosing spines with disruption of the discs, as shown in Fig.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…9 There are also a few previous reports of successful percutaneous vertebroplasties for vertebral fractures in patients with DISH. 12,23 The present study showed that fractures of the most distal or distal-adjacent vertebrae of ankylosing spines were stabilized by bone healing in 51/89 patients (57.3%) 6 months after BKP. In addition, fractures of the vertebrae adjacent to the ankylosing spines with disruption of the discs, as shown in Fig.…”
Section: Discussionsupporting
confidence: 49%
“…Early surgical stabilization is therefore recommended for vertebral fractures in patients with DISH, due to the risk of instability and secondary delayed neurological deterioration. 10 Fusion surgery for OVFs in ankylosing spines with DISH has been previously reported; [11][12][13][14] however, minimally invasive treatment is desirable due to the high incidence of postoperative complications reported in patients with DISH. 15,16 Although the treatment of ankylosing spinal fractures requires fusion surgery similar to that required for long bone fractures, the indications for BKP in fractures of the terminal or adjacent vertebral bodies of ankylosing spines remain controversial.…”
mentioning
confidence: 99%
“…The VBS procedure, introduced as a new option for vertebral cement augmentation, has an advantage over BKP in that the stent maintains the restored vertebral body height after intravertebral reduction [11]. Some reports have demonstrated the usefulness of cement augmentation for vertebral fractures in ankylosing spines, including DISH [12][13][14]. Tsuchikawa et al reported improved VAS and Oswestry Disability Index (ODI) scores in patients undergoing BKP surgery for fractures of the distal or distally adjacent vertebrae of DISH [14].…”
Section: Discussionmentioning
confidence: 99%
“…62 These results were also demonstrated when kyphoplasty was used instead of vertebroplasty. 63,64 Additionally, bracing with anti-osteoporotic treatment is believed to contribute to improved quality of life for the patient. 63 However, Tsuchikawa et al recommend avoiding this technique in patients with a difference ≥ 10° in the wedge angle of the fractured vertebrae between the supine and sitting positions as it was associated with delayed healing.…”
Section: Vertebroplasty and Kyphoplastymentioning
confidence: 99%